Antimicrobial susceptibility and molecular characterization of Salmonella enterica serovar Indiana from foods, patients, and environments in China during 2007–2016. (January 2022) - Zhang, Zengfeng; He, Shoukui; Xu, Xuebin; Chang, Jiang; Zhan, Zeqiang; Cui, Yan; Shi, Chunlei; Shi, Xianming
Abstract: Salmonella enterica serovar Indiana has become a widely prevalent non-typhoidal serovar in China in recent years. To improve the understanding of antimicrobial resistance and genetic bias in this emerging pathogen, a total of 214 S . Indiana isolates from foods, patients, and the environments in China from 2007 to 2016 were characterized for antimicrobial susceptibility, antimicrobial resistance-determining factors, and molecular typing. It was found that 208 (97.2%) exhibited resistance to ciprofloxacin, and 102 (47.7%) isolates to ceftriaxone. Ciprofloxacin resistance increased from 82.4% in 2007–2008 to 100.0% in 2015–2016. Ceftriaxone resistance increased from 29.4% in 2007–2008 to 47.1% in 2015–2016. In particular, the proportion of multidrug-resistant (MDR) S. Indiana isolates increased from 64.7% in 2007–2008 to 91.4% in 2015–2016. Mutations in the quinolone resistance determining region (QRDR) ( gyr A and par C), plasmid-mediated quinolone resistance (PMQR) genes [ aac(6')-Ib-cr, oqx AB, qnr A, qnr S, qnr B and qep A], extended-spectrum beta-lactamase (ESBL) genes ( bla OXA, bla CTX-M, bla TEM, bla CMY and bla VEB ), and class I integrons were identified in these S. Indiana isolates, along with transposon units of ΔIS Ecp1 - bla CTX-M-65 -IS 903B, IS Ecp1 -IS Vsa5 - bla CTX-M-14 -IS 903B, and IS Ecp1 - bla CTX-M-55/15 -Δ orf 477. To our knowledge, the ESBL gene bla VEB was identified in Salmonella for the first time. Diverse plasmid types (IncHI2, IncN, IncA/C, IncFIB, IncI1 and IncFII) were identified in these isolates, among which IncHI2-type plasmid (49.1%) was the most common type in S . Indiana. Multilocus sequence typing (MLST) showed a single ST17 in S . Indiana. Pulsed-field gel electrophoresis (PFGE) results showed that there was a genotypic diversity, and some clones might have existed in S . Indiana between patients and foods for several years. These findings suggested that the frequent emergence of S . Indiana isolates with resistance to ciprofloxacin and ceftriaxone would pose a huge threat to food safety and public health. Highlights: ∙ Ciprofloxacin and ceftriaxone co-resistant isolates were found. ∙ESBLs genes, PMQR genes with mutations in QRDR and class I integrons were observed. ∙ bla VEB was identified in Salmonella for the first time. ∙IS Ecp1, IS Vsa5 and IS 903B was adjacent to bla CTX-M. ∙ST17 and genotypic diversity were identified in S. Indiana.